2020
DOI: 10.1145/3368314
|View full text |Cite
|
Sign up to set email alerts
|

Non-line-of-sight Reconstruction Using Efficient Transient Rendering

Abstract: Object Object(a) (b) (c) Fig. 1. (a) The challenge of looking around the corner deals with the recovery of information about objects beyond the direct line of sight. In this illustration of a setting proposed by Velten et al. [2012], an unknown object is located in front of a wall, but additional obstacles occlude the object from any optical devices like light sources or cameras. Our only source of information are therefore indirect reflections off other surfaces (here, a planar "wall"). A point on the wall th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 42 publications
(74 reference statements)
0
26
0
Order By: Relevance
“…Finally, an interesting extension would be to NLOS imaging, especially given the latest developments exploiting computational techniques for image information retrieval from temporal data [16,[40][41][42][43] and the availability of public data-sets [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an interesting extension would be to NLOS imaging, especially given the latest developments exploiting computational techniques for image information retrieval from temporal data [16,[40][41][42][43] and the availability of public data-sets [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Very little work is proposed to provide a dataset for NLOS imaging. Jarabo et al [14] introduce a framework for transient rendering, which has been adopted for NLOS data simulation in many literatures [22,12,19]. For example, Klein et al [17] introduce a synthetic dataset for various NLOS reconstruction problems yet with only 16 data samples.…”
Section: Nlos Imaging Systems and Datasetsmentioning
confidence: 99%
“…This line of work follows the approach proposed by Kirmani et al [16] and demonstrated experimentally by Velten and colleagues [39]: very short laser pulses illuminate a visible surface facing the hidden scene, then the scattered light reflected back onto such visible surface is captured. The hidden scene is then reconstructed using backprojection algorithms and heuristic filters [39,17,2,4], or inverting simplified light transport models [31,1,33,45,10,47,13]. These methods have usually been demonstrated in simple isolated scenes with little indirect illumination from interreflections.…”
Section: Related Workmentioning
confidence: 99%